Age at menarche in schoolgirls with and without excess weight - Silvia D. Castilho; Luciana B. Nucci (Brazilian Society of Pediatrics, 2015)
Objective: To evaluate the age at menarche of girls, with or without weight excess, attending private and public schools in a city in Southeastern Brazil. Methods: This was a cross‐sectional study comparing the age at menarche of 750 girls from private schools with 921 students from public schools, aged between 7 and 18 years. The menarche was reported by the status quo method and age at menarche was estimated by logarithmic transformation. The girls were grouped according to body mass index (BMI) cut‐off points: (thin + normal) and (overweight + obesity). In order to ensure that they belonged to different strata, 328 parents of these schools answered a questionnaire to rate the student's socioeconomic level. Results: Menarche was reported by 883 girls. Although they belonged to different classes (p < 0.001), there was no difference in the nutritional diagnosis (p = 0.104) between them. There was also no difference in age at menarche between the girls studying in private (12.1 years, 95% CI: 12.0‐12.2) and public schools (12.2 years, 95% CI:12.1‐12.3; p = 0.383). When evaluated by nutritional status, there was difference only in the age at menarche between girls from private schools with excess weight and without excess weight (11.6 and 12.3 years; p < 0.001). The girls with excess weight attending private schools also had earlier an menarche than those attending public schools (respectively, 11.6 and 12.1 years; p = 0.016). Conclusions: Although the students from private schools belonged to a higher socioeconomic status, there is currently no longer a large gap between them and girls from public schools regarding nutritional and socioeconomic factors that may influence the age at menarche.